Taṭwīr Ta`līm Kitāb “Khulāṣah Nur al-Yaqīn” Bi Istirātījiyah al-Jahīrah (Vocalize) `Alā Asās al-Madkhal al-Kullī Wa Ṭarīqah al-Qirā’ah Li Tarqiyah Qudrah aṭ-Ṭalabah `Alā Fahm an-Nushush (Dirāsah al-Baḥṡ Wa at-Taṭwīr Bi Ma`had Insan Qur’ani Aceh Besar) - Rizka Safitri (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2023)
The strategy is a plan, method, or activity designed to enhance students’ learning and achieve certain educational goals. Strategy relates to the execution of the idea, planning, and execution of an activity within a certain period. This study aims to determine the learning process using the Al-Jahera Strategy (Vocalize) at Dayah Insan Qurani Aceh Besar, and to determine the effectiveness of using the Al-Jahera Strategy (Vocalize) based on the Whole Language Approach and Reading Method to improve students' ability to understand text in the book of Khulasha Noor Al Yaqeen, also to find out the response of students’ class VIII at Dayah Insan Qurani Aceh Besar. The Research Method referred to Research and Development (R&D) with ADDIE models. The object of this Research is 31 students (VIII-A) for the 2022/2023 academic year at Dayah Insan Qurani, Aceh Besar. The result of this study, the researcher finds a new Teaching Strategy, namely